Perbedaan Kadar Trigliserida Pada Penderita Diabetes Melitus Tipe 2 Dengan Penyakit Jantung Koroner Dan Tanpa Penyakit Jantung Koroner Di RSUD Dr. Moewardi - Purwanto, Denny Eka Putri; , dr. Iin Novita N.M, M. Sc., Sp. PD (2017)
ABSTRACT THE DIFFERENCE IN THE LEVELS OF TRIGLYCERIDES IN PEOPLE WITH TYPE 2 DIABETES MELLITUS WITH CORONARY HEART DISEASE AND CORONARY HEART DISEASE IN PROVINCIAL HOSPITAL Dr. MOEWARDI Denny Eka Putri Purwanto , Iin Novita Nurhidayati Mahmuda Background: Coronary heart disease is one of cardiovascular disease that causes the death globally. The mechanism of coronary heart disease in people with diabetes mellitus are very complex and can influenced by changes in the lipid profile. Increased of triglyceride levels associated with hiperinsulinemia and is a risk factor for coronary heart disease. Objective: To know the distinction of triglycerides levels in type 2 diabetes mellitus patients with coronary heart disease and without coronary heart disease in Dr. Moewardi Hospitals Surakarta. Methods: An analytical observational research with cross sectional study. The subject of research is the secondary data from 70 people with diabetes mellitus type 2 which consists of 35 subjects with coronary heart disease and 35 subject without coronary heart disease who listed in the medical record of patients hospitalization period September 2015 until September 2016 in Dr. Moewardi Hospitals Surakarta. Statistical analysis used independent T test. Results: Based on the analysis of data obtained by mean ± SD triglyceride levels of type 2 diabetes mellitus with coronary heart disease was 192,17 ± 45,500 and mean ± SD of type 2 diabetes mellitus without coronary heart disease was 132,03 ± 49,628 with P value = 0.000. Conclusion: There was distinction of triglyceride levels in type 2 diabetes mellitus patients with coronary heart disease and without coronary heart disease in Dr. Moewardi Hospitals. Key words: Triglyceride Levels, type 2 Diabetes mellitus, coronary heart disease